Nonsuicidal Self-Injury and Suicide: The Role of Life Events in Clinical and Non-Clinical Populations of Adolescents - Horváth, Lili Olga; Győri, Dóra; Komáromy, Dániel; Mészáros, Gergely; Szentiványi, Dóra; Balázs, Judit (Frontiers in Psychiatry, 2020)
Background: Nonsuicidal self-injury (NSSI) is highly prevalent in clinical and non-clinical populations of adolescents. Several studies have supported both the distinction and the strong association between NSSI and suicidal behaviour. Although there is a great deal of data on the role of life events in both suicidal behaviour and NSSI, few studies have assessed the role of life events in the NSSI-suicidal behaviour relationship. Our aims were to explore the relationship between NSSI and suicidal behaviour, and the possible moderating role of stressful life events in a clinical and non-clinical adolescent population. Method: A clinical (n=202) and a nonclinical (n=161) population of adolescents, aged 13-18 years were assessed. The Mini International Neuropsychiatric Interview Kid, Deliberate Self-Harm Inventory and the Life Events List were used. Group differences related to suicidal behaviour, NSSI, and life events were tested with Wilcoxon tests. Two- and three-way interactions were tested with negative binomial regression models including zero-inflation parameter. Results: The prevalence of suicidal behaviour (W=7306, p<.001), NSSI (W=9652, p<.001) and life events (W=10410 p<.001) were significantly higher in the clinical than in the non-clinical group. Between number of life events and NSSI, a moderate effect size (.38, 95%CI [.28, .46]) was found. The main effect of NSSI (χ2(1)=109.65, p<.001) and group membership (χ2(1)=39.13, p<.001) predicted suicidal behaviour; the main effect of quantity of life events did not explain suicidal behaviour. The interaction between NSSI and number of life events (χ2(1)=10.49, p<.01) was associated with suicidal behaviour. Among interpersonal, non-interpersonal events and adverse childhood circumstances, only interpersonal events were associated with both suicidal behaviour (χ2(1)=6.08, p<.05) and had a moderating effect (χ2(1)=8.59, p<.01) on the NSSI–suicidal behaviour relationship. Patterns of the effects of life events on the NSSI–suicidal behaviour relationship did not differ in the two groups. Conclusion: Our results confirm the importance of prevention and intervention of NSSI, considering its high prevalence and frequent co-occurrence with suicidal behaviour in both clinical and non-clinical adolescent populations. Moreover, to support NSSI and suicide prevention, we would like to highlight the importance of stressful life events, especially those associated with interpersonal conflicts, require special attention.